2020
DOI: 10.1038/s41598-020-65762-y
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of In Vitro to In Vivo Translation of a TYK2 Inhibitor That Shows Cross Species Potency Differences

Abstract: Translation of modulation of drug target activity to therapeutic effect is a critical aspect for all drug discovery programs. In this work we describe the profiling of a non-receptor tyrosine-protein kinase (TYK2) inhibitor which shows a functionally relevant potency shift between human and preclinical species (e.g. murine, dog, macaque) in both biochemical and cellular assays. Comparison of the structure and sequence homology of TYK2 between human and preclinical species within the ATP binding site highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…In this mouse model, the murine TYK2 gene was modified by introducing a humanizing point mutation in order to change amino acid 980 of murine TYK2 protein from valine to isoleucine. This was done in order to compensate for an observed species potency shift driven by this amino acid difference between human and preclinical species . Oral treatment with 22 at 30, 10, and 3 mg/kg, once per day (QD) reduced clinical end points associated with skin inflammation in this model (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In this mouse model, the murine TYK2 gene was modified by introducing a humanizing point mutation in order to change amino acid 980 of murine TYK2 protein from valine to isoleucine. This was done in order to compensate for an observed species potency shift driven by this amino acid difference between human and preclinical species . Oral treatment with 22 at 30, 10, and 3 mg/kg, once per day (QD) reduced clinical end points associated with skin inflammation in this model (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Oral treatment with 13 formulated as a spray dried dispersion significantly inhibited ear swelling in imiquimod-induced psoriasis-like humanized mouse models carrying a TYK2 V980I mutation . This mouse model was used to compensate for potency shift across species driven by this amino acid difference between human and preclinical species . Compound 13 (ropsacitinib, PF-06826647) is currently in phase II clinical trials to treat multiple autoimmune disorders (Table ).…”
Section: Tyk2 Inhibitorsmentioning
confidence: 99%
“…While this may seem low, it is on par with the average conservation of orthologous genes between the species ( Makałowski et al, 1996 ). To this point, one recent study examined the inter-species sequence homology of the Tyk2 ATP binding site in the kinase domain, revealing only one amino acid substitution out of 42 amino acids between species ( Gerstenberger et al, 2020b ). Here, human isoleucine (I) 960 was found to be substituted by a valine in mouse at the equivalent position (V980).…”
Section: Using Mice To Study Tyk2: Pros and Consmentioning
confidence: 99%
“…In addition, there have been publications involving dual TYK2 and JAK1 catalytic inhibitors; SAR-20347, blocked psoriasis-like skin inflammation in mice ( Works et al, 2014 ) and PF-06700841 (brepocitinib), was found to be protective against adjuvant-induced arthritis in rats ( Fensome et al, 2018 ). Despite this apparent success, this line of TYK2/JAK1 dual inhibitors were found to have drastically reduced potency against murine and rat Tyk2 compared to human TYK2 due a single amino acid substitution in the ATP binding site ( Gerstenberger et al, 2020b ), as discussed above. Using the humanized Tyk2-V980I mouse, a TYK2-selective inhibitor, PF-06826647, was shown to be effective against murine dermatitis ( Gerstenberger et al, 2020a ).…”
Section: Tyrosine Kinase 2 a Once Neglected Therapeutic Targetmentioning
confidence: 99%